(untitled) (Current Horticulture, 2024)
The nutrient responsive nature of fruit crops predisposes them to multiple nutrient deficiencies, resulting in their economic manifestations on quality production is a formidable challenge to nutritionists. The crop-based soil health care is basic to any fruit nutrition program. But, still a bigger challenge lies in diagnosing the genesis of any nutrient deficiency at the right stage. It just starts and in the field itself. So that nutritional problems are addressed in the current season’s crop. Various nutrient supply chain management for fruit crops have their own merits and demerits, but all of them address 4R nutrient stewardship principles. However, ISFM is still considered as another form of regenerative agriculture. Our current efforts should concentrate on these issues, so that soil health care becomes a grower’s movement with visibility on long-term fruit industry.